Influence Factors of Pressure Attenuation Gradient and its Reservoir Forming Control - A Case Study of Bonan Sag in Bohai Bay Basin. Issue 2 (July 2021) - Feng, Yuelin; Zhang, Tianjiao; Wang, Yongshi; Mu, Xing; Xiong, Wei; An, Tianxia; Wang, Yong
Abstract: As the dynamic condition of oil and gas migration, the change rate of overpressure has a certain relationship with the mode of oil and gas migration. In order to quantitatively identify the mode of oil and gas migration in overpressure basins, the influence of different transmission modes on pressure attenuation gradient is simulated, and the application and discussion are carried out in Bonan sag of Bohai Bay Basin. The influence of different transmission modes on the pressure attenuation gradient is discussed by single factor simulation method. Taking Bonan sag as an example, the process of overpressure fluid migration and accumulation is discussed combined with the evolution process of pressure attenuation gradient. The results show that fault activity has the greatest influence on pressure attenuation gradient, followed by fault dip angle and fault distance. the influence degree of physical properties of skeleton sand body, sand body dip angle and sand body thickness on pressure attenuation gradient decreases in turn; For the fault-sand consistent transport, it mainly depends on the combined effect of the dip angle and resistance of the transport system. The critical value of the fault or sand body transport in Bonan sag is 58.8MPa/km. On this basis, combined with the evolution law of pressure attenuation gradient, it is considered that the overpressure fluid in the deep sag migrates along the oil source fault to the fault terrace zone and the overpressure center distribution of the oil and gas ring in the deep sag. The overpressure oil and gas mainly migrate laterally along the sand body, and the oil and gas are distributed contiguously. In gentle slope zone, oil and gas distribute sporadically at structural height.